The association of bilateral intraorbital giant mucoceles and inverted papilloma: A case report - Albayrak, Serdal; Üçler, Necati; Arici, Lütfü; Bozgeyik, Zülküf; Kaplan, Metin (Gulhane Medical School, University of Health Sciences, 2013)
The association of bilateral intraorbital giant mucoceles and inverted papilloma: a case report Inverted papillomas are a benign neoplasm of nasal cavity and paranasal sinuses and may cause local destruction. Although mucoceles are pathologies likely extending to intracranial and intraorbital spaces. We presented the case with giant bilateral intraorbital mucoceles, already having three times surgery for recurrence of the nasal inverted papilloma. After bicoronal incision, our case underwent excision of bilateral giant intraorbital mucoceles and inverted papilloma with the endoscopic assistance. No recurrence was shown in terms of mucoceles and inverted papilloma in the follow-up after surgery. After inverted papilloma and mucocele surgeries, the recurrence rate is high. Therefore, residues from the lesions and obliteration of sinuses are important during surgery. As an aid to the conventional surgery, the use of endoscopy in especially larger lesions will improve surgical success. © Gülhane Askeri Ti{dotless}p Akademisi 2013.
İki tarafli intraorbital dev mukosel ile inverted papilom birlikteli?i: Vaka sunumu
Keywords: Frontal sinus; Inverted papilloma; Mucocele; Orbita